Introducing all-inkjet-printed microneedles for in-vivo biosensing - Giulio Rosati; Patricia Batista Deroco; Matheus Guitti Bonando; Gustavo G. Dalkiranis; Kumara Cordero-Edwards; Gabriel Maroli; Lauro Tatsuo Kubota; Osvaldo N. Oliveira; Lúcia Akemi Miyazato Saito; Cecilia de Carvalho Castro Silva; Arben Merkoçi (Scientific Reports)
Abstract Microneedles are mainly used for pain-free drug administration and in biosensing for wearable systems. They are also promising for fields such as agronomy for precision farming, but their fabrication is not straightforward, often requiring expensive equipment and cleanroom protocols, being unsuitable for mass production. Here, we report a new and simple method for the scalable fabrication of all-inkjet-printed conductive microneedles based on silver nanoparticles (extensible to any other metallic nanoparticle ink) and a simple example of their application for monitoring the electrochemical properties of plants.